Otitis Media Practice During the COVID-19 Pandemic - Marom, Tal; Pitaro, Jacob; Shah, Udayan K.; Torretta, Sara; Marchisio, Paola; Kumar, Ayan T.; Barth, Patrick C.; Tamir, Sharon Ovnat (Frontiers in Cellular and Infection Microbiology, 2022)
The global coronavirus disease-2019 (COVID-19) pandemic has changed the prevalence and management of many pediatric infectious diseases, including acute otitis media (AOM). Coronaviruses are a group of RNA viruses that cause respiratory tract infections in humans. Prior to the COVID-19 pandemic, coronavirus serotypes OC43, 229E, HKU1 and NL63 were infrequently detected in middle ear fluid (MEF) specimens and nasopharyngeal aspirates in children with AOM during the 1990s and 2000s, and were associated with a mild course of the disease. At times when CoV was detected in OM cases, the overall viral load was relatively low. The new severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the causative pathogen responsible for the eruption of the COVID-19 global pandemic. Following the pandemic declaration in many countries and by the World Health Organization in March 2020, preventive proactive measures were imposed to limit COVID-19. These included social distancing; lockdowns; closure of workplaces; kindergartens and schools; increased hygiene; use of antiseptics and alcohol-based gels; frequent temperature measurements and wearing masks. These measures were not the only ones taken, as hospitals and clinics tried to minimize treating non-urgent medical referrals such as OM, and elective surgical procedures were cancelled, such as ventilating tube insertion (VTI). These changes and regulations altered the way OM is practiced during the COVID-19 pandemic. Advents in technology allowed a vast use of telemedicine technologies for OM, however accuracy of AOM diagnosis in those encounters was in doubt, and antibiotic prescription rates were still reported to be high. There was an overall decrease in AOM episodes and admissions rates, and with high spontaneous resolution rates of MEF in children, and a reduction in VTI surgeries. Despite an initial fear regarding viral shedding during myringotomy, the procedure was shown to be safe. Special draping techniques for otologic surgery were suggested. Other aspects of OM practice included presentation of adult patients with AOM who tested positive for SARS-2-CoV, and its detection in MEF samples in living patients and in the mucosa of the middle ear and mastoid in post-mortem specimens.